2019
DOI: 10.1097/nt.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Genes Coding for Folate-Related Enzymes and Colorectal Cancer

Abstract: This review examined the association between folate and risk of colorectal cancer and single-nucleotide polymorphisms in 4 genes coding for folate metabolism–related enzymes may be involved. Individuals with single-nucleotide polymorphisms in these key enzymes in the folate pathways may need different amounts of dietary folate to prevent colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…An increase in dietary folate has a protective effect against CRC prior to the onset of neoplastic foci, while, after the initial lesions, the consumption of dietary folate may increase tumorigenesis. 63 Folate metabolism can affect methyl distribution and alter DNA methylation and DNA synthesis. Some studies have indicated that dietary folate deficiency increased CRC risk, 64 but folate may protect only folate‐deficient individuals against the risk of CRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in dietary folate has a protective effect against CRC prior to the onset of neoplastic foci, while, after the initial lesions, the consumption of dietary folate may increase tumorigenesis. 63 Folate metabolism can affect methyl distribution and alter DNA methylation and DNA synthesis. Some studies have indicated that dietary folate deficiency increased CRC risk, 64 but folate may protect only folate‐deficient individuals against the risk of CRC.…”
Section: Resultsmentioning
confidence: 99%
“…Folate, known as vitamin B₉, may play a dual role in colon carcinogenesis. An increase in dietary folate has a protective effect against CRC prior to the onset of neoplastic foci, while, after the initial lesions, the consumption of dietary folate may increase tumorigenesis 63 . Folate metabolism can affect methyl distribution and alter DNA methylation and DNA synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Folate deficiency reduces the availability of methyl group and conversion of homocysteine to methionine. Hyperhomocysteinemia inhibits DNA methylation which may increase the risk of cancer (Gholamalizadeh et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%